Quale scuola per il XXI secolo? Un'identità possibile - Franco Cambi (Firenze University Press, 2017)
Which kind of school can and must work for the social and cultural transfor-mations in effect? School should be democratic, open, critical and educational. This school has some challenges and tasks that should be re achieve: the knowledge more sophisticated, formae mentis more plural and dialectical, the self-care more important for every subjects.